Pharmacogenomics of Medications Commonly Used in the Intensive Care Unit - Zhou, Shuqin; Skaar, Debra J.; Jacobson, Pamala A.; Huang, R. Stephanie (Frontiers in Pharmacology, 2018)
In the intensive care unit (ICU) setting, where highly variable and insufficient drug efficacies, as well as frequent and unpredictable adverse drug reactions (ADRs) occur, pharmacogenomics (PGx) offers an opportunity to improve health outcomes. However, PGx has not been fully evaluated in the ICU, partly due to lack of knowledge of how genetic markers may affect drug therapy. To fill in this gap, we conducted a review to summarize the PGx information for the medications commonly encountered in the ICU.